Technological change and the finance wage premium - Ata Can Bertay; José Carre\~no; Harry Huizinga; Burak Uras; Nathanael Vellekoop (Leibniz Institute for Financial Research SAFE, 2022)
This paper utilizes a comprehensive worker-firm panel for the Netherlands to quantify the impact of ICT capital-skill complementarity on the finance wage premium after the Global Financial Crisis. We apply additive worker and firm fixed-effect models to account for unobserved worker- and firm-heterogeneity and show that firm fixed-effects correct for a downward bias in the estimated finance wage premium. Our results indicate a sizable finance wage premium for both fixed- and full-hourly wages. The complementarity between ICT capital spending and the share of high skill workers at the firm-level reduces the full-wage premium considerably and the fixed-wage premium almost entirely.
Keywords: G20; J24; J31; O33; 330; finance wage premium; worker-firm panels; skill-biased technological change